PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL DAN MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJAR MATA PELAJARAN AKIDAH AKHLAK DI KELAS VII SMP MUHAMMADIYAH WATUKELIR SUKOHARJO TAHUN AJARAN 2021/2022 - Reyna Yulia Agustin; Muhammad Ja'far Nashir; Muhammad Fatchurrohman; Meti Fatimah (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to determine how the influence of the use of audio visual, learning motivation, student learning outcomes and is there any effect of using audio-visual media and learning motivation on student learning outcomes. This type of research is quantitative research. The subjects in this study were 7th grade students of SMP Muhammadiyah Watukelir Sukoharjo. Data collection techniques used in this study were interviews, questionnaires, observation and documentation. While the data analysis using multiple linear regression. Measuring instrument validity test uses the Product Moment Person correlation, and the reliability test uses Cronbach's Alpha formula. The analysis requirements test consists of a data normality test, a linearity test and multicollinearity test. Hypothesis testing using multiple linear regression analysis. The results of this study show that audio-visual media and learning motivation have an effect on student learning outcomes.